Respon Perubahan Tarif Pajak Penghasilan, Insentif Dan Non-Insentif Pajak Terhadap Manajemen Laba - Abdul Slamet; Provita Wijayanti (Conference In Business, Accounting, And Management (CBAM), 2012)
Tax is an obligation that must be paid by the company, the greater the income the company the greater the tax due. Management expects the tax payment detail to allow management to do the engineering to minimize the income tax burden. This study aims to examine the effects of changes in income tax rates that Law. 36 of 2008 on Income Tax on discretionary accrual due to a decrease in income tax rates between 2009 and the Agency for the year 2010 is the year 2009 by 28% and in 2010 dropped to 25%. In addition, this study also aims to determine the impact of tax and non tax incentives as well as the percentage of shares traded on the Stock Exchange of earnings management behavior.Â  Sample of this study is manufacturing companies listed on the Indonesia Stock Exchange, which has published its financial statements from 2009-2010. Methods of analysis in this study using multiple regression analysis to determine the effect of independent variables earnings pressure, debt level, earnings bath, firm size, managerial ownership and the percentage of shares) against the dependent variable (discretionary accruals) and using independent sample t-test for the different test equipment. independent sample t-test was used to examine differences in the level of discretionary accruals between 2009 and 2010 after a decline in income tax rates. The results showed that before and after the reduction in tax rates, the management was not convicted of discretionary accruals to make savings income. This suggests that management in Indonesia did not take action to make opportunistic earnings management in order to decrease the tax rate Agency 2010. From the regression results of tax incentives and the percentage of shares traded on the Stock Exchange a significant effect on discretionary accruals, non-tax incentives only to have a significant earnings pressure on discretionary accruals, while the level of debt, earnings bath, firm size and managerial ownership has no significant effect on discretionary accruals.Â Keywords :Changes in tax rates, and discretionary accruals.